Reducing The Number of Intermediate Stock by Implementing Just-In-Time & Pulling System - Nuraini, Lisna; Ratum, Athina Sakina (Journal of Integrated System, 2024)
In tire manufacturing process in PT. XYZ, there is an area called the Intermediate Area in the Building - Curing area where WIP materials are temporarily stored before proceeding to the Curing process. The capacity of Intermediate Area is 15000 pcs, and the daily production volume approximately 20000 pcs. As a result, more space in the Intermediate Area is required to accommodate the increasing tire production planning. In this study, JIT & Pull system improvement process is carried out by following the PDCA cycle methodology. The implementation of the JIT done by determining standard for the number of intermediate stocks, whereas the Pull system implementation done by setting the standard material handling cycle time standard for one cycle. To keep the improvement runs according to the plan, the guidance sheet is made as the reference of the process. These improvements done to achieve the objective which is to reduce the number of stocks in the Intermediate Area by up to 834 pcs per day and reduce the total cycle time from 110 minutes to 90 minutes. Therefore, the main contribution of this research is to reduce the number of WIP materials in intermediate area and reduce the excessive transportation in the material handling process.